Examining the therapeutic potential and side effects of calcium channel blockers in mortality and morbidity of patients with stroke: A systematic review of pre-clinical and clinical studies - Sevak Hatamian; Asad Abdi; Fatemeh Sadat Seyedi Asl; Armin Tafazolimoghadam; Arian Tavasol; Seyed Ali Mousavi Nejad; Reza Madadi; Zohre Tajabadi; Mina Dehghani; Najmeh Ahmadpoor; Mobina Fathi; Mohammadreza Hajiesmaeili; et al. (IBRO Neuroscience Reports)
Background: Blood pressure control is one of the basic steps in preventing stroke and cerebrovascular events. Calcium channel blockers are the first-line drugs in hypertension control. On the other hand, the stroke recovery phase depends on activating calcium channels and N-methyl-D-aspartate (NMDA) receptors. Considering these issues, one of the interdisciplinary challenges of neurology and cardiology is the use of these drugs in hypertensive patients with cerebrovascular accident (CVA) risk and their uses after these events. Objectives: This study's primary goal is to evaluate the effects of calcium channel blockers on reducing the risk, mortality, morbidity, and long-term outcomes of cerebrovascular events. Material and Methods: We conducted this systematic literature review by searching PubMed, Scopus, and Google Scholar databases. Our inclusion criteria were randomized clinical trials, cohort studies, case-cross-over studies, case reports, and in-vitro and animal studies in which they evaluated the effects of calcium channel blockers on the CVA risk and mortality, morbidity, and long-term outcomes of stroke. Our exclusion criteria were review studies with no adequate data and non-English articles. Articles that met our criteria were included in the initial search. After the title and abstract screening, 56 human and animal studies were selected to be discussed in this article. Results: Among 56 selected studies, 33 were human studies, 23 were animal experiments, and one study was carried out both on animals and humans. A total of 1,860,234 patients were enrolled in 24 human studies. A total of 717,131 patients in 22 studies received CCBs. Two studies did not report the number of patients who underwent treatment with CCBs. Among 24 studies, 11 reported favorable outcomes following CCB administration, and two studies reported neuroprotective effects for CCBs without any adverse outcome in stroke patients. Five studies demonstrated that CCBs were associated with adverse outcomes. One study showed favorable and unfavorable outcomes compared to other antihypertensive agents. Stroke was reported in two studies following CCB overdose. Three studies have reported that CCBs had no significant effect on stroke risk, mortality, or long-term outcomes. In animal studies, a total of 813 animals were enrolled in 19 studies. Two studies were in vitro using mammalian cells and enzymes, and one study was ex-vivo. Among 24 studies, 18 (75 %) reported beneficial outcomes following treatment with CCBs, three (12.5 %) revealed both favorable and unfavorable results, two (8.3 %) demonstrated adverse outcomes, and one (4.2 %) showed no effect. Conclusion: Based on the evidence from human and animal studies, authors conclude that CCBs are associated with a lower risk of stroke, lower mortality risk, and improved long-term neurological and other clinical outcomes.